Predlog direktive o sanaciji in reševanju zavarovalnic - Černovšek, Juš (Podjetje in delo, 2022)
With the aim of unifying the legislation in the European Union and avoiding further fragmentation of procedures relating to the recovery and resolution of insurance and reinsurance undertakings, the European Commission has on 22 September 2021 adopted a proposal for a directive that establishes a framework for the recovery and resolution of insurance and reinsurance undertakings (IRRD). The proposal is in a lot of ways similar to the regulation in the banking field, which was established with the Bank Recovery and Resolution Directive (BRRD). The newly proposed recovery and resolution directive will introduce a lot of additional obligations for the industry and for the regulators on the European and, consequently, on the Slovenian insurance market. The In cooperation with the regulators, insurance companies will have to prepare and annually update their recovery plans. It is also assumed that a new resolution authority will be formed, which will be responsible for preparing resolution plans for insurance and reinsurance undertakings and taking necessary action if insurance companies get into financial difficulties.